Implications of a Surge in Capital Inflows : Available tools and Consequences for the Conduct of Monetary Policy - Lee, Jang-Yung (IMF Working Papers; Working Paper, 1996)
This paper seeks to extend discussion of monetary policy instruments to the situation of a country faced with major capital inflows when the process of domestic financial liberalization is incomplete. It briefly summarizes the recent usage of traditional monetary instruments, discusses the practical limits to classic sterilization measures as well as the pros and cons of using other supplementary measures including tax-based controls on capital inflows. It also examines the efficacy of such measures in Chile, Colombia, Indonesia, Korea, Spain, and Thailand. The conclusion is that, for a time and as a transitional measure, a country may find it opportune to supplement the traditional instruments with certain 'belt and braces' measures including, in some instances, indirect (tax-based) capital controls.